Untying knots: the importance of historical and social contextualization for the enjoyment of textile art (Palíndromo, 2024)
The present work aims to provide an overview of the evolution of perceptions regarding textile art over time, in the search for clarifying certain notions that still influence the judgment of works located in this category. The importance of the historical and social contextualization of a given practice was discussed – in this case, artistic production involving textile fibers – so that it can be enjoyed to its full potential. The procedure adopted was bibliographical research. An approximation of artistic practice involving textile fibers with handicrafts and feminine activities was identified. This association began during the Middle Ages and intensified from the Renaissance onwards, coinciding with the idea of the artist as a creative genius in counterpoint to the figure of the craftsman. Concomitant to this process, the ideal of women as housewives, whose activities were restricted to the domestic environment, became associated with textile practices. Subsequently, modernist canons made it difficult to accept textile works as art objects, precisely because of their association with crafts and a feminine context. From the 1960s and throughout the 1970s, eminently in North America, the work of several artists who used the textile medium contributed to fostering discussion around the artistic practice studied and made it possible for the traditional defining concepts of work of art were questioned.
Keywords: textile art; crafts; tapestry